Dual-beam polarization interferometry resolves mechanistic aspects of polyelectrolyte adsorption - Lane, Thomas J (Langmuir : the ACS journal of surfaces and colloids, 2008)
The electrostatically driven binding dynamics of a polyelectrolyte multilayer (PEMU) film was investigated in real-time using dual-beam polarization interferometry (DPI) and independently supported by quartz crystal microbalance with dissipation monitoring (QCM-D) studies. Multilayer assemblies of the polyanions poly[1-[4[(3-carboxy-4-hydroxyphenylazo)benzenesulfonamido]-1,2-ethanediyl sodium salt] (PAZO) and poly(styrene sulfonate) (PSS) were respectively constructed with the polycation poly(ethylenimine) (PEI) on anionic functionalized substrates using the layer-by-layer electrostatic self-assembly method. DPI measurements indicate that polyelectrolyte adsorption occurs in three distinct stages. In the first stage, for approximately 5 s, coil-like segments of polyanion partially tether to the surface of the oppositely charged PEI. In the second stage, these coils unfurl over a period of approximately 10 s to cover the surface resulting in an increase in average density of the film. During the final adsorption step, the surface-bound polyelectrolyte diffuses into the multilayer assembly, exposing the surface to further deposition. This last step occurs over a much longer time period and results in a highly interpenetrated film containing a charge-overcompensated region at the film surface